1997
DOI: 10.1177/096120339700600304
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis in systemic lupus erythematosus

Abstract: We studied the frequency, location, clinical and histopathological features, associated manifestations, and prognosis of vasculitides in a cohort of 667 SLE patients. Exclusion of patients with previous vasculitis or insufficient information left 540 patients, 194 of whom has vasculitis (incidence density: 0.053 new cases/person/year, cumulative incidence of 0.051 at one year, 0.232 at 5 years and 0.411 at 10 years). Vasculitis was confirmed by biopsy in 46 cases, by arteriography in five, and by both in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
150
1
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(169 citation statements)
references
References 32 publications
5
150
1
7
Order By: Relevance
“…Pulmonary capillaritis with alveolar hemorrhage is a rare but severe manifestation of the disease. Excluding these disorders, vasculitis was noted in approximately 11-36% of SLE patients in two large retrospective studies, and mainly affected the small vessels of the skin (7,8). The most common skin lesions were erythematous punctate lesions on the fingertips and palms (such as in this case), followed by palpable purpura.…”
Section: Systemic Vasculitis In Slementioning
confidence: 79%
See 2 more Smart Citations
“…Pulmonary capillaritis with alveolar hemorrhage is a rare but severe manifestation of the disease. Excluding these disorders, vasculitis was noted in approximately 11-36% of SLE patients in two large retrospective studies, and mainly affected the small vessels of the skin (7,8). The most common skin lesions were erythematous punctate lesions on the fingertips and palms (such as in this case), followed by palpable purpura.…”
Section: Systemic Vasculitis In Slementioning
confidence: 79%
“…The most common skin lesions were erythematous punctate lesions on the fingertips and palms (such as in this case), followed by palpable purpura. Histologically, leukocytoclastic followed by lymphocytic vasculitis were the most common pathologies (8). Medium-vessel vasculitis comprised 14 -15% of all vasculitis cases and presented mainly with mononeuritis multiplex, and less commonly with digital necrosis and visceral involvement, with necrotizing vasculitis of the vessel wall on histology.…”
Section: Systemic Vasculitis In Slementioning
confidence: 95%
See 1 more Smart Citation
“…Intestinal vasculitis has been reported to be 0.2% in a study by Drenkard et al of 540 SLE patients. 8 Other studies have shown an incidence rate of up to 53%. A recent chart review study of 175 patients by C-K Lee et al showed that vasculitis was the most common cause of acute abdominal pain in SLE patients (found in 45% of patients).…”
Section: Small and Large Bowelmentioning
confidence: 99%
“…3 Several risk factors have been identified with digital ulcers in SLE, including duration of lupus, male gender, atherosclerosis, vasculitis, and AAS. 4 Liu et al 5 demonstrated that duration of disease, the presence of Raynaud's phenomenon, and high serum CRP levels were determinants of digital ulcer development in a cohort of 2,600 lupus patients. When we looked at the risk factors in our patient, she had a 10-year history of lupus, but her disease activity was under control with small oral doses of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%